2008
DOI: 10.1021/jm070663s
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors of the Gardos Channel for the Treatment of Sickle Cell Disease

Abstract: Sickle cell disease (SCD) is a hereditary condition characterized by deformation of red blood cells (RBCs). This phenomenon is due to the presence of abnormal hemoglobin that polymerizes upon deoxygenation. This effect is exacerbated when dehydrated RBCs experience a loss of both water and potassium salts. One critical pathway for the regulation of potassium efflux from RBCs is the Gardos channel, a calcium-activated potassium channel. This paper describes the synthesis and biological evaluation of a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…It has been shown that repeated cycles of sickling and unsickling lead to activation of the Gardos channel (K Ca 3.1), a calcium-activated potassium efflux channel, which is a major factor in RBC dehydration and reduced deformability and increased fragility [4], [5]. Dehydration increases the intracellular concentration of Hb which enhances the rate of polymerization [6], [7], [8]. Red blood cell fragility results in hemolysis in SCD and other hemolytic diseases [9], [10], diabetes, and transfusion of older stored blood; which in turn can lead directly to inflammation [11], [12], [13], and platelet activation [14], [15], [16], [17], [18], [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that repeated cycles of sickling and unsickling lead to activation of the Gardos channel (K Ca 3.1), a calcium-activated potassium efflux channel, which is a major factor in RBC dehydration and reduced deformability and increased fragility [4], [5]. Dehydration increases the intracellular concentration of Hb which enhances the rate of polymerization [6], [7], [8]. Red blood cell fragility results in hemolysis in SCD and other hemolytic diseases [9], [10], diabetes, and transfusion of older stored blood; which in turn can lead directly to inflammation [11], [12], [13], and platelet activation [14], [15], [16], [17], [18], [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds prevented hemolysis and sickle cell formation in vivo, in a transgenic mouse model [69,70].…”
Section: Inhibition Of Erythrocyte Dehydrationmentioning
confidence: 98%
“…Other potential indications for KCa3.1 inhibition are sickle cell disease (Brugnara, 2003) and secretory diarrhea in humans and farm animals (Rufo et al, 1997). Research groups in both the pharmaceutical industry and academia have identified several classes of potent and selective KCa3.1 blockers including the triarylmethanes senicapoc (triarylmethanes 2,2-bis-(4-fluorophenyl)-2-phenylacetamide) (McNaughton-Smith et al, 2008) and diphenylmethyl]-1H-pyrazole) , the benzothiazione NS6180 (4- [[3-(trifluoromethyl)phenyl]methyl]-2H-1,4-benzothiazin-3(4H)-one) (Strøbaek et al, 2013), and a series of dihydropyridine isosteric 4-phenyl-pyrans and cyclohexadienes (Urbahns et al, 2005). Senicapoc, which was in phase-3 clinical trials for sickle cell anemia, where it failed for lack of efficacy in reducing the number of painful sickling attacks (Ataga et al, 2011), demonstrated that KCa3.1 inhibitors are safe and well tolerated in humans.…”
Section: Introductionmentioning
confidence: 99%